An alternative aggregation method for a life cycle impact assessment using an analytical hierarchy process - Hafizan, C. (Elsevier Ltd, 2016)
The purpose of this paper is to propose an alternative methodology for aggregation in a life cycle assessment (LCA). The comprehensive aggregation method is based on a damage approach and done through an analytical hierarchy process. Consistency analysis is also presented to justify the reliability of the judgements and the magnitude of change in the values developed. A case study of electricity generation is applied to demonstrate its applicability in LCA study within a Malaysian context. Results from this case study show that the weighting value is higher compared to global and European values; however, they are consistent as in the case of product ranking towards greener products. Regional impacts such as particulate matter formation and photochemical oxidant formation have higher score compared to global impacts such as climate change. The results show that the method is simple and replicable.